Henry Clark Corbin papers - Corbin, Henry Clark, 1842-1909.
Correspondence, memoranda, reports, speeches, writings including an autobiography, autograph albums, scrapbooks, photographs, and other papers concerning Corbin's military career from the Civil War to his retirement in 1906 and his life in Washington, D.C. Subjects include the Spanish American War; administration of the Philippines, 1900-1906; the China Relief Expedition, 1900-1901; the presidential inaugurations of James A. Garfield, 1881, and William McKinley, 1901; the social and political affairs of Corbin's family, a prominent family in Washington, D.C., at the turn of the century; and Corbin's wife, Edythe Agnes Patten Corbin, and other Patten (Patton) family members.
Correspondents include Adna Romanza Chaffee, George B. Cortelyou, Charles Henry Grosvenor, Rutherford Birchard Hayes, William Loeb, William Ludlom, John James McCook, Theodore Roosevelt, Theodore Schwan, William Rufus Shafter, William H. Taft, and Leonard Wood.
In part, typewritten transcripts.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chaffee, Adna Romanza, -- 1842-1914 -- Correspondence; Corbin, Edythe Agnes Patten; Cortelyou, George B. -- 1862-1940 -- Correspondence; Garfield, James A. -- 1831-1881.; Grosvenor, Charles Henry, -- 1833-1917 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Loeb, William, -- 1866-1937 -- Correspondence; Ludlom, William -- Correspondence; McCook, John James, -- 1843-1927 -- Correspondence; McKinley, William, -- 1843-1901.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Schwan, Theodore -- Correspondence; Shafter, William Rufus, -- 1835-1906 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Corbin family; Patton family; United States. -- Army -- Foreign service -- Philippines; International relief -- China; Presidents -- United States -- Inauguration; Spanish-American War, 1898.; Philippines -- History -- 1898-1946.; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Politics and government -- 1878-1967.; Washington (D.C.) -- Social life and customs; Army officers